Differences in Physical Activity and Built Environment Perceptions between Younger and Older Adults Living in The Same Rural - Charilaos Papadopoulos; Brent J Twaddle (Intelektual Pustaka Media Utama, 2016)
This study examined associations between perceptions and physical activity of younger and older adults residing in the same rural/small town community. Thirty-two adults completed interviews about their community and their physical activity. Both groups perceived their neighborhood as pleasant and safe to be active. Fewer older adults perceived their neighborhood as having sidewalks. Younger adults reported being more vigorously active and they were more often utilizing private membership clubs for physical activity. Older adults utilized more public recreational facilities. These results suggest that higher perceived quality of the neighborhood built environment can enhance participation in moderate exercise in older adults.